2014
DOI: 10.1007/s10529-014-1589-z
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of intracoronary autologous bone marrow stem cell transfer as an adjunct to percutaneous coronary intervention in patients with acute myocardial infarction

Abstract: The efficacy of post-percutaneous coronary intervention (PCI) intracoronary injection with bone marrow mesenchymal stem cells (BMSCs) in patients with acute myocardial infarction (AMI) remains controversial. Here, 58 patients with AMI undergoing PCI were randomly divided into two groups: BMSC and control groups. Autologous BSMCs were then generated in vitro from the BMSC patients. After transplantation, left ventricular ejection fraction (LVEF), left ventricular end-diastolic dimensions (LVDd), and infarct siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Of the 23 included studies, 11 evaluated AMI ( n = 509 patients) and 12 evaluated IHF ( n = 639 patients) (Table ). Of these studies, eight were RCTs that evaluated AMI ( n = 429 patients) and five were RCTs that evaluated IHF ( n = 472 patients) . The number of evaluated patients who received MSCs ranged from 9 to 58 patients for the AMI studies and from 6 to 107 patients for the IHF studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 23 included studies, 11 evaluated AMI ( n = 509 patients) and 12 evaluated IHF ( n = 639 patients) (Table ). Of these studies, eight were RCTs that evaluated AMI ( n = 429 patients) and five were RCTs that evaluated IHF ( n = 472 patients) . The number of evaluated patients who received MSCs ranged from 9 to 58 patients for the AMI studies and from 6 to 107 patients for the IHF studies.…”
Section: Resultsmentioning
confidence: 99%
“…Follow‐up duration ranged from 6 to 60 months. Of the studies evaluating AMI, seven studies specified safety and four studies specified efficacy as their primary outcome. Secondary outcomes assessed included safety or efficacy .…”
Section: Resultsmentioning
confidence: 99%
“…However, the beneficial effects of MSCs on global cardiac function in a clinical setting remain uncertain. Several randomized controlled clinical trials showed a significantly improved LVEF after MSC transplantation [110][111][112], whereas others did not observe differences between SC treated and control groups [74,[113][114][115][116][117]. Furthermore, neither a recent meta-analysis of pre-clinical studies [118] nor comparative clinical studies [119,120] detected significant differences of autologous versus allogeneic MSCs on cardiac function.…”
Section: Bm-derived Mscsmentioning
confidence: 99%
“…Total events Heterogeneity: χ 2 = 11.63, df = 11 (p = 0.39); I 2 = 5% Test for overall effect: Z = 0.72 (p = 0.47) Test for subgroup differences: χ 2 = 4.37, df = 1 (p = 0.04); I 2 Table A).…”
Section: Total (95% Cl)mentioning
confidence: 99%
“…The sensitivity analysis excluding 1 study at a time confirmed the results concerning all analyses in terms of direction and magnitude of statistical significance. The statistical heterogeneity(I 2 ) for LVEF vanished dramatically from 93% to 27%, indicating low heterogeneity among the majority of the studies included, except for the study by Wang et al 2 Considering LVEF as the primary endpoint for almost all studies, this study was excluded in the following statistical analyses. After the exclusion, the heterogeneity for most cardiac parameters and all clinical outcomes was low.…”
Section: Sensitivity Analysismentioning
confidence: 99%